Síntese do feromônio sexual e respostas eletrofisiológicas frente ao óleo essencial de Psidium guajava de Tryrinteina arnobia - Neppe, Tiago (2008)
The study of semiochemicals involves the knowledge of different interaction levels between organisms and allows us to understand communication mechanisms and the action of specific compounds in the insect behavior. The eucalyptus-brown-looper, Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae) is considered an important pest in Brazil for native plants, as Psidium guajava, and exotic plants, as for example Eucalyptus species. This work describes the racemic synthesis of T. arnobia sex pheromone, 3,4-epoxy-6,9-heneicodiene, in 11 steps and 27% overall yield. The synthesized compound, tested by electroantennography (EAG) with male and female antennae at concentration of 100mg/mL, demonstrated identical bioactivity for both sex. We also obtained essential oils from leaves of wild white guava (P. guajava), by steam distillation, in order to investigate its electrophysiological action in T. arnobia. It was observed that the composition of young and old leaves of guava is different. Nevertheless, the EAG essential oil analyzes towards male and female antennae have shown that they are very bioactive. The synthetic pheromone and the kairomones isolated from the essential oil may allow us to understand the action of these substances in the insect behavior, through laboratory and field tests observation. Confirmed the substances attractive actions, their use in pest management will become very important.